Evaluation and selection of Online Food Delivery (OFD) companies in Perlis using fuzzy Analytical Hierarchy Process (AHP) / Zurina Kasim and Nur Anis Liyana Muhamad Rosli - Kasim, Zurina; Muhamad Rosli, Nur Anis Liyana (UiTM Cawangan Perlis, 2022)
The COVID-19 pandemic has accelerated the global expansion of online food delivery (OFD) services. Food delivery services are comparable to courier services in that the ordered food is delivered to customers by workers or rider delivery companies. As the number of OFD companies continues to rise, the selection of OFD companies, such as GrabFood, Foodpanda, Halo Delivery, and others, is extremely competitive. Customers must choose carefully which OFD companies offer the best services. The objectives of this research are to investigate the evaluation criteria for OFD companies, then evaluate the OFD companies based on the evaluation criteria and rank the best OFD companies that provide the best services to customers in Perlis based on certain criteria. As a result, this study proposes a solution to this problem by developing a technique from multi criteria decision making (MCDM) known as the Fuzzy Analytical Hierarchy Process (FAHP) to determine the relative importance of criteria used in ranking OFD services. This study's findings indicate that Foodpanda is the most preferred food delivery service, followed by Grabfood and Halo Delivery. The most crucial main criteria is the economy, with discounts and offers as the priority sub-criteria. The second most important criterion is service quality, and the last is technology.